Remarks on Determinant Line Bundles, Chern-Simons Forms and Invariants - Dupont, Johan L.; Johansen, Flemming Lindblad (MATHEMATICA SCANDINAVICA, 2002)
We study generalized determinant line bundles for families of principal bundles and connections. We explore the connections of this line bundle and give conditions for the uniqueness of such. Furthermore we construct for families of bundles and connections over manifolds with boundary, a generalized Chern-Simons invariant as a section of a determinant line bundle.